Love and Solitude - Confrontations - Domeracki, Piotr (Filozofia Chrześcijańska, 2014)
The article raises an issue of love and loneliness confronted with opinion, that love is the only antidote for loneliness. Its author is submitting this thesis to a precise research. The source wish of love is motivated by aiming at avoiding loneliness. The loneliness seems to be more primary phenomenon to love. This does not necessarily mean that it is not true that love can overcome loneliness. Loneliness can only give way under the pressure of perfect love. It is an attribute of God. A man authentically immersed in that Love has a capacity for overcoming of his loneliness.